2016
DOI: 10.1111/acel.12436
|View full text |Cite
|
Sign up to set email alerts
|

High dietary advanced glycation end products are associated with poorer spatial learning and accelerated Aβ deposition in an Alzheimer mouse model

Abstract: SummaryThere is growing evidence of the involvement of advanced glycation end products (AGEs) in the pathogenesis of neurodegenerative processes including Alzheimer's disease (AD) and their function as a seed for the aggregation of Aβ, a hallmark feature of AD. AGEs are formed endogenously and exogenously during heating and irradiation of foods. We here examined the effect of a diet high in AGEs in the context of an irradiated diet on memory, insoluble Aβ42, AGEs levels in hippocampus, on expression of the rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 41 publications
3
63
2
Order By: Relevance
“…Glycation reaction leads to alteration in the structure and function of biomolecules particularly proteins. AGE formation is known as a key element in diabetes complications [4146]. …”
Section: Resultsmentioning
confidence: 99%
“…Glycation reaction leads to alteration in the structure and function of biomolecules particularly proteins. AGE formation is known as a key element in diabetes complications [4146]. …”
Section: Resultsmentioning
confidence: 99%
“…Trauma can significantly increase expression of the alarmin HMBG1 (Horst et al, 2016), which in turn activates an inflammatory cascade by stimulating multiple receptors including RAGE and TLR4 (Mazarati et al, 2011). A recent study showed that AD-like model mice, on a diet enriched in AGEs due to irradiation, exhibit significant memory dysfunction, accompanied with the hippocampal deposition of insoluble Aβ42 fragment and AGEs (Lubitz et al, 2016). This latter finding was consistent with the notion that Aβ can activate microglia and induce neurotoxicity by RAGE binding (Yan et al, 1996).…”
Section: Abiotic Stress and Admentioning
confidence: 99%
“…The diet containing a regular AGE product content was prepared without exposure to heat, while the diet with a high AGE product content consisted of the same chow exposed to gamma irradiation from a cobalt-60 source as per standard procedure. Both diets were therefore nutritionally equivalent and differed only in the content of AGE products (for a more detail, see [38]). Diets were pelleted by the manufacturer and kept at room temperature.…”
Section: Dietsmentioning
confidence: 99%
“…After evaluation of their cognitive functions at 11 months of age, animals were anesthetized with isoflurane (Baxter Healthcare Corp., Deerfield, IL, USA) and sacrificed by decapitation. The right brain hemisphere was fixed and then used for histological/morphological analyses (the results will be published separately along with those of behavioral testing using the Morris water maze [38]). The left hemisphere was rapidly frozen in liquid nitrogen, stored at -80°C and then used for neurochemical analyses.…”
Section: Animalsmentioning
confidence: 99%